ASPEK HUKUM PENGEMBANGAN USAHA KELOMPOK USAHA PERHUTANAN SOSIAL (KUPS) KELOMPOK TANI HUTAN (KTH) TIRTE URIP LOMBOK TENGAH NTB - Raodah, Putri; Mulyana, Septira Putri; Fathoni, Lalu Achmad; Wardani, Nizia Kusuma (Faculty of Law, University of Mataram, 2024)
This research examines the legal aspects of SFBGs business development at FFGs Tirte Urip. Increasing institutional capacity is needed to develop the SFBGs business at FFGs Tirte Urip. The method is that the SFBGs at FFGs Tirte Urip must prepare and ratify the SFBGs management plan document and SFBGs internal regulations. Implementation must be carried out towards integrated efforts to assist SFBGs business development by various parties. Villages must include SFBGs business development efforts in the VMTDPs (Village Medium Term Development Plan), VGWPs (Village Government Work Plan) Village Regulations, and Rambitan Village APBDes. Hence, Rambitan village government has a legal basis for taking a position as the leading actor driving efforts to develop the SFBGs business. The specificity of SFBGs business development at FFGs Tirte Urip is the inclusion of FFGs Tirte Urip in the Mandalika Agroforestry IAD; this is an integrated and collaborative program between ministries/agencies, provincial, district/city governments, and related parties as stated in Presidential Decree 28/2023. So, the SFBGs at FFG Tirte Urip must take a lot of initiative to implement Article 12 and the social forestry acceleration action plan listed in the attachment to Presidential Decree 28/2023.